2009
DOI: 10.1158/1078-0432.ccr-08-2880
|View full text |Cite
|
Sign up to set email alerts
|

Rectal Mucosal Microvascular Blood Supply Increase Is Associated with Colonic Neoplasia

Abstract: Purpose: Endoscopic examination has proven effective in both detecting and preventing colorectal cancer; however, only about a quarter of eligible patients undergo screening. Even if the compliance rate increased, limited endoscopic capacity and cost would be prohibitive. There is a need for an accurate method to target colonoscopy to those most at risk of harboring colonic neoplasia. Exploiting field carcinogenesis seems to be a promising avenue. Our group recently reported that an early increase in blood sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 39 publications
2
32
0
Order By: Relevance
“…Using polarization-gated spectroscopy, we have previously shown that early increases in bloody supply associated with carcinogenesis are more prominent at superficial tissue layers. 7,26 Low coherence interferometry has been used to demonstrate that the most significant changes in nuclear diameter in the AOM-treated rat occur at a depth of 35 μm. 35 In the present study, both the copolarization and crosspolarization m parameter were statistically significant indicators of concurrent neoplasia, suggesting diffuse alterations throughout mucosa and submucosa in the shape of the index correlation function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using polarization-gated spectroscopy, we have previously shown that early increases in bloody supply associated with carcinogenesis are more prominent at superficial tissue layers. 7,26 Low coherence interferometry has been used to demonstrate that the most significant changes in nuclear diameter in the AOM-treated rat occur at a depth of 35 μm. 35 In the present study, both the copolarization and crosspolarization m parameter were statistically significant indicators of concurrent neoplasia, suggesting diffuse alterations throughout mucosa and submucosa in the shape of the index correlation function.…”
Section: Discussionmentioning
confidence: 99%
“…Methods to separate the absorbance spectrum from the scattering spectrum f ðm; cλ 2m−4 Þ have been further described in detail in previous publications. 7,17,26 The precise functional form of f ðm; cλ 2m−4 Þ was determined using the MC methods described in Secs. 2.1 and 2.2 and is described in the results section.…”
Section: Polarization-gated System and Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Our optical and histological investigations in human patients and animal models of colon carcinogenesis have shown diagnostic alterations in hemoglobin concentration that are present in the mucosa but attenuated at deeper submucosal depths. [1][2][3][4][5] Studies with angle-resolved low-coherence interferometry demonstrate that elevation of nuclear diameter associated with dysplasia in Barrett's esophagus was only detectable at a depth of 200 to 300 μm and not observable at 0 to 100 μm or 100 to 200 μm. 6 Several fiber-optic probe modalities have been developed to target the mucosal layer with a wide field of view.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] These methods have proven successful in diagnosing epithelial lesions including those in the colon, oral, and other types of mucosae. 1,2,9,13,[15][16][17][18] On the other hand, diffuse reflectance spectroscopy (DRS) methods typically have a sampling depth on the order of several millimeters and are consequently not very selective to the mucosal layer. However, the deeper sampling depth of DRS may be advantageous for other applications.…”
Section: Introductionmentioning
confidence: 99%